Rethinking the Role of Nitrogen and Phosphorus in the Eutrophication of Aquatic Ecosystems - Karl Havens; Thomas Frazer (EDIS)
For many years, environmental agencies have sought to improve the water quality of lakes and estuaries by reducing inputs of phosphorus. New research indicates that we must reduce both phosphorus and nitrogen to reverse eutrophication symptoms. This 3-page fact sheet was written by Karl Havens and Thomas Frazer, and published by the UF Department of Sea Grant, June 2012.